The Art of Diplomacy in Vocally Negotiating Barn Owl Siblings - Ducouret, Pauline; Romano, Andrea; Dreiss, Amélie N.; Marmaroli, Patrick; Falourd, Xavier; Roulin, Alexandre (Frontiers in Ecology and Evolution, 2019)
To resolve conflicts over limited resources, animals often communicate about their motivation to compete. When signals are transient, the resolution of conflicts may be achieved after an interactive process, with each contestant adjusting its signalling level according to the rival’s behaviour. Unfortunately, the importance of the real-time signal adjustment in conflict resolution remains understudied, especially using experimental approaches. Here we developed a novel “automatic interactive playback” that interacts real-time with a live individual. It allowed us to experimentally test the efficacy of different behavioural strategies to dominate conflicts in nestling barn owls (Tyto alba). In this species, nestlings vocally negotiate for priority access to the impending food item in the absence of parents. Two opposite vocal strategies were tested for their prospects of success: under the “matching” vs. “mismatching” strategy, the playback behaves in the same vs. opposed way as the nestling, respectively. We evaluated how these two strategies affected the two main negotiation parameters: call duration and call rate. We found that the best strategies to reduce the nestling’s vocalizations and hence dominate the negotiation are to match the call duration of the opponent and to mismatch its call rate. However, the latter strategy is the only one that allowed the playback to dominate the vocal interaction by inducing the opponent to become totally silent. Therefore, to prevail in a negotiation session, barn owl nestlings should delay the transmission of signals rather than simultaneously escalate vocalizations as commonly observed in animal competitive interactions. In addition, we showed that matching call duration and mismatching call rate require a larger investment by the playback, in terms of number and duration of calls, than the less effective strategies. Assuming that vocalisations are costly, this suggests that such behavioural strategies are honest. Our results highlight the importance of real-time signalling adjustment in communication processes over resource competition and emphasize the power of using interactive playback settings to investigate conflict resolution in animals.